Entrepreneurship in property management. - Loh, Celeste Shi Min. (2008)
This report is introducing the business opportunities in property management industry to the entrepreneurs in Singapore. Issues on entrepreneurial activities in Singapore, conditions of the property management industry in Singapore, and entrepreneurship opportunities in the property management industry are being addressed. The advantages of venturing into this industry are included, and recommendations to aspiring entrepreneurs in this industry are also discussed.